2001
DOI: 10.1055/s-2001-14213
|View full text |Cite
|
Sign up to set email alerts
|

Erwartungen und Zufriedenheit von Patienten während eines stationären Krankenhausaufenthaltes

Abstract: Since cost-benefit is a basic need in running a hospital today, financial resources should be enhanced in the spheres which are equally medically important for fulfilling the expectations of the patients. Therefore, the number of staff and the qualification of the medical professionals should be financed instead of supporting architectural and room design. Accordingly, the patients' main criteria for choosing a hospital is the medical equipment provided and the qualification of the medical staff. In conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
2
0
4
Order By: Relevance
“…In accordance with this, Baberg et al [17] found that patients focus more on how knowledgeable and attentive their doctors are than they do on medical equipment or whether or not they have a single room.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In accordance with this, Baberg et al [17] found that patients focus more on how knowledgeable and attentive their doctors are than they do on medical equipment or whether or not they have a single room.…”
Section: Discussionmentioning
confidence: 76%
“…This is not only an ethical imperative but, nowadays, also an important factor of competition between health care institutions. Therefore, studies of patient satisfaction have often been performed from a perspective of quality assurance [16,17]. Unfortunately, the quality assurance managers behind these efforts seem at times to be unfamiliar with survey research [1,18], resulting in a "quality literature of poor quality".…”
Section: Discussionmentioning
confidence: 99%
“…3Ergebnisse der Patientenzufriedenheit können zur Kliniksteuerung beitragen, wenn bestimmte methodische Voraussetzungen erfüllt werden [3,9,21,23,26,32].…”
Section: Konsequenz Für Klinik Und Praxisunclassified
“…In der vorliegenden Studie wurden methodische Anforderungen an Patientenbefragungen berücksichtigt [3,9,11,14,17,19 Abb. 6 Unzufriedenheit "Zuwendung durch Pflege und Ärzte" -Korrelation mit Arztrotation.…”
Section: Introductionunclassified
“…Kliniken und niedergelassener ¾rzte einschließlich Zahnmedizin bilden die Autoren: Baberg [93], Beer [94], Geiger [95], Hollederer [96], Huber [97], Ihle [98], Lange [99], Müller [100], Schneeweiss [101], Schubert [102], Tegtbur [103], Tretter [104], Wilm [105] und Zimmer [106].…”
Section: Introductionunclassified